VIP induces the decidualization program and conditions the immunoregulation of the implantation process - Grasso, Esteban Nicolas (2018)
The decidualization process involves phenotype and functional changes on endometrial cells and the modulation of mediators with immunoregulatory properties as the vasoactive intestinal peptide (VIP). We investigate VIP contribution to the decidualization program and to immunoregulation throughout the human embryo implantation process. The decidualization of Human endometrial stromal cell line (HESC) with Medroxyprogesterone-dibutyryl-cAMP increased VIP/VPAC-receptors system. In fact, VIP could induce decidualization increasing differentiation markers (IGFBP1, PRL, KLF13/KLF9 ratio, CXCL12, CXCL8 and CCL2) and allowing Blastocyst-like spheroids (BLS) invasion in an in vitro model of embryo implantation. Focus on the tolerogenic effects, decidualized cells induced a semi-mature profile on maternal dendritic cells; restrained CD4+ cells recruitment while increased regulatory T-cells recruitment. Interestingly, the human blastocyst conditioned media from developmentally impaired embryos diminished the invasion and T-regulatory cells recruitment in these settings. These evidences suggest that VIP contributes to the implantation process inducing decidualization, allowing BLS invasion and favoring a tolerogenic micro-environment.